Report of the Industrial Licensing Policy Inquiry Committee Appendices Volume I - Planning Commission (Planning Commission, 1969)
The Government of India set out in their Resolution dated the 6th, April 1948, the policy which they proposed to pursue in the industrial field. The Resolution emphasised the importance to the economy of securing a continuous increase in production and its equitable distribution, and pointed out that the Slate must play a progressively active role in the development of industries. It laid down that besides arms and ammunition, atomic energy and railway transport, which would be the monopoly of the Central Government, the State would be exclusively responsible for the establishment of new undertakings in six basic industries—except where, in the national interest, the State itself found it necessary to secure the co-operation of private enterprise. The rest of the industrial field was left open to private enterprise though it was made clear that the State would also progressively participate in this field.
Government of India, Department of Industrial Development, Ministry of Industrial Development, Internal Trade and Company Affairs